PENGARUH PENYIMPANGAN GERAK SUMBU AXIS XYZ PADA CNC ROUTER 3018 - Iskandar, Iskandar; Sani, Almadora Anwar; Suryana, Didi; Utami, Ogi Meita; Zainuddin, Zainuddin; HB, Indra; Nugraha, Muhammad (Politeknik Negeri Sriwijaya, Indonesia, 2022)
The industry is currently transitioning into the Industrial Revolution 4.0 era. Technology disruption is becoming more prevalent. The major goal of this industrial revolution is to maintain the flow of essentials and goods. Technology advancements demand equipment, such as CNC machines, that can be utilized to produce the required components. Using a CNC Router 3018 machine for this investigation. Data from previously generated Computer Aided Design (CAD) programming is used during the production of specimen objects. It is then imported into the Computer Aided Manufacturing (CAM) programming software in order to generate the NC Code and operate the machine in accordance with the intended form. This research was done to find out how the CNC Router 3018's motion deviation on the XYZ axis affected things. Acrylic resin with a 10 mm thickness is used in the substance. The results of the measurement data analysis were then put through a